Polymerization of N‐Vinyl Formamide in Homogeneous and Heterogeneous Media and Surfactant Free Emulsion Polymerization of MMA Using Polyvinylamine as Stabilizer. Issue 1 (November 2013) - Zataray, J.; Aguirre, A.; de la Cal, J.C.; Leiza, J.R.; Moritz, Hans‐Ulrich; Pauer, Werner
Summary This work considers the homogeneous aqueous phase polymerization of n‐vinyl formamide(NVF). Thus, the effect of temperature, initiator and monomer concentration in the kinetics and molar mass distribution (MMD) of the polyNVF produced was experimentally assessed. SEC‐MALS analysis was misleading because anomalous elution was found due to interaction of the polyNVF chains with the column. This was solved by analyzing the polyNVF by asymmetric‐flow field flow fractionation chromatography coupled with multi‐angle light scattering and differential refractive index, AF4/MALS/RI. The second part of this work considered the synthesis of nanoparticles based on polyNVF. Two routes were explored. In the first one the inverse microemulsion photopolymerization of NVF was attempted and polyNVF dispersions in isopar M with solids content of 18 wt% and particle sizes in the range 50–70 nm with average molar masses of several millions were obtained. In the second route PolyNVF produced in homogeneous aqueous phase was hydrolyzed to yield polyvinyl amine, PVAm. The resulting water soluble polymers were used to produce polymethyl methacrylate, PMMA, nanoparticles by surfactant free emulsion polymerization initiated by tert‐butyl hydroperoxide TBHP. Stable pH responsive PMMA cationic nanoparticles with amino functionalities in the surface were easily produced.